Analisis Faktor yang Mempengaruhi Kesuksesan Pemasaran Teh Teko di Kota Denpasar: Pendekatan SWOT dan Marketing Mix 7P - I Gede Putra Perdana; Putu Rana Rajendra (Jurnal Ilmiah Satyagraha, 2026)
The "Teh Kekinian" beverage industry in Denpasar City shows rapid growth but is accompanied by a saturated level of competition. Amidst many brands that failed to survive, Teh Teko was able to expand and maintain its existence as a local player. This study aims to analyze the factors that influence the marketing success of Teh Teko in Denpasar City through the 7P marketing mix approach and SWOT analysis. The method used is descriptive qualitative with data collection techniques through field observations, interviews with managers, and distribution of questionnaires to consumers. The results show that Teh Teko's success is driven by the optimization of Price elements (affordable prices of Rp5,000 - Rp15,000) and Place (strategic location in densely populated areas) which are highly relevant to the characteristics of hot weather in Denpasar. Based on the SWOT analysis, Teh Teko is in an aggressive position but needs to be aware of the threat of changes in healthy lifestyles. The study concludes that the integration between operational efficiency (Process) and the strength of local identity (People & Product) is the main key to winning the market. Suggestions included low-sugar product innovation and strengthening digital branding to maintain consumer loyalty in the future.